"God's word does not change as trends do" – contemporary discourses on homosexuality in Swedish Christianity. Issue 1 (2nd January 2020) - Carlström, Charlotta
ABSTRACT: Throughout history, Christianity has regarded homosexuality as abnormal and something beyond what can be fully accepted. In this article, I investigate how homosexuality has been discussed within the Swedish evangelical churches from 2009 until 2019, in the largest Swedish Christian newspaper, Dagen (The Day). It is not possible to speak of a hegemonic discourse on homosexuality – rather the 188 articles analyzed show a multiplicity of stances towards homosexuality. The articles constitute a field of tension where several discourses struggle for space and interpretative prerogative. Inspired by Foucauldian discourse analysis, I identify three ways in which the writers understand homosexuality in relation to their faith: the Affirmative Contextual Discourse, the Middle Way Discourse and the Conservative Discourse. The overall view in each discourse is characterized by heteronormativity. Positions within the Conservative Discourse are given most space in the newspaper when it comes to homosexuality.